The Role of Elementary School Teachers' Professional Competencies in Optimizing Learning Quality - Bendriyanti, Rita Prima; Dewi, Citra; Suwarni, Suwarni; Sukirdi, Sukirdi (Universitas Trunojoyo Madura, 2025)
The professional competence of elementary school teachers plays a crucial role in optimizing the quality of learning at the primary level. Competent teachers not only master the subject matter but are also skilled in designing, implementing, and evaluating learning effectively. This study aims to analyze the contribution of elementary teachers' professional competence in improving learning quality through a literature review. The method used is a library study, analyzing various relevant journals and articles. The findings indicate that pedagogical mastery, professionalism, and innovative teaching skills significantly influence student learning outcomes. Teachers with strong pedagogical abilities can adapt teaching methods to students' needs, fostering better understanding and engagement. Additionally, professional competence enables teachers to utilize technology and creative learning strategies, making lessons more interactive and effective. Furthermore, continuous assessment and feedback from competent teachers help identify students' weaknesses and improve learning strategies. Continuous teacher training and qualification enhancement should be prioritized. Workshops, certification programs, and mentoring can help teachers stay updated with the latest educational developments. By improving teachers' professional competence, schools can ensure higher learning quality, better student achievement, and long-term educational success. Investing in teacher development is essential for building a strong foundation in elementary education